Systematic errors arising from polarization imperfections in measurements of the electron’s electric dipole moment - Ho,C; Wright,S; Sauer,B; Tarbutt,M (Physical Review Research, 2023)
The electron’s electric dipole moment (eEDM) can be determined by polarizing the spin of an atom or a molecule and then measuring the spin precession frequency in an applied electric field. Radiation is used to polarize the spin and then analyze the precession angle, and the measurement is often sensitive to the polarization of this radiation. We show how systematic errors can arise when both the polarization of the radiation and the magnitude of the electric field are imperfectly controlled. We derive approximate analytical expressions for these errors, confirm their accuracy numerically, and show how they can be corrected empirically. We consider spin manipulation using single-photon pulses, Raman pulses, and Stimulated Raman Adiabatic Passage (STIRAP), and show that STIRAP provides better immunity to these systematic errors. An experimental study of these errors partly supports our findings but also reveals another potential error that is not captured by this analysis.